'Why aren't you on PrEP? You're a gay man': reification of HIV 'risk' influences perception and behaviour of young sexual minority men and medical providers. Issue 1 (2nd January 2023) - Hascher, Kevin; Jaiswal, Jessica; Lorenzo, Julianna; LoSchiavo, Caleb; Burton, Wanda; Cox, Amanda; Dunlap, Kandyce; Grin, Benjamin; Griffin, Marybec; Halkitis, Perry N.
Abstract: Public health models and medical interventions have often failed to consider the impact of reductionist HIV 'risk' discourse on how sexual minority men interpret, enact and embody biomedical knowledge in the context of sexual encounters. The aim of this study was to use an anthropological lens to examine sexual minority men's perception of HIV risk and experience within the medical system in order to examine the influence of risk discourse on their health, behaviour and social norms. In-depth interviews ( n  = 43) were conducted with a racially, ethnically and socioeconomically diverse sample of young sexual minority men and explored HIV-related beliefs and experiences, as well as their interactions with healthcare providers. Findings suggest that the stigmatisation of behaviours associated with HIV appears to be shaped by three key forces: healthcare provider perceptions of sexual minority men as inherently 'risky', community slut-shaming, and perceptions of risk related to anal sex positioning. Stigmatising notions of risk appear to be embodied through sexual health practices and identities vis-à-vis preferred anal sex positions and appear to influence condom use and PrEP initiation.